Analisis Kualitas Butir Soal HOTS pada Mata Pelajaran Biologi yang Diberikan pada Siswa Kelas 12 dan Dievaluasi Menggunakan Aplikasi Anates - Lestari, Iing Dwi; Yumna K, Ryke Zain; Dewi, Siti Alda Lusia; M, Early Sri; Nurhalizah, Putri; Rosalina, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to develop and describe an effective assessment instrument. This type of research is Research and Development, while the data collection technique uses test techniques. Data analysis techniques use qualitative and quantitative analysis. The results of this study are as follows: there are 13 significant assessment items and 12 items that are not yet significant. Therefore, there are still some items that need to be improved to be used as a suitable assessment instrument, both theoretically and empirically. Suitable theoretically means that it has fulfilled the aspects of construction, language, and material. While suitable empirically means through validity testing, reliability, difficulty level, discriminant power, and distractor quality analysis. An assessment instrument can be considered suitable if it meets the characteristics of Higher Order Thinking Skills; and the assessment instrument can be used as a tool to evaluate learning outcomes because it can differentiate between students with high, medium, and low abilities.